Main trends of immune effects triggered by nanomedicines in preclinical studies - Halamoda-Kenzaoui, Blanka (Int J Nanomedicine, 2018)
The application of nanotechnology to emerging medicinal products is a crucial parameter for the implementation of personalized medicine. For example, sophisticated drug delivery systems can target the diseased tissue by recognizing patient-specific biomarkers while carrying pharmacologically active molecules. However, such nanomedicines can be recognized by the immune system as foreign triggering unexpected biological reactions. The anticipation of the immunogenic potential of emerging nanotechnology-based products in the preclinical phase is challenging due to high interspecies variations between the immune systems of laboratory animals and humans. A close monitoring of the scientific literature is required to better understand the relationship between various immune reactions and the diversity of nanomedicines currently in the development pipeline. We have reviewed the most frequent immune reactions induced by the nanomaterials in vivo and have identified the main effects triggered by lipid-based, polymer-based and inorganic nanoparticles, as the main categories of nanomaterials used in medicine. According to our results, almost 50% of the investigated nanomaterials induced effects related to the activation of the immune system. Among them, complement activation-related hypersensitivity reactions and activation of adaptive immune response were the most frequent effects reported for the lipid-based nanoparticles. However, many of these effects are not or are only partially covered by the current regulatory framework applicable for nanomedicines. In addition, we extracted the most relevant nanospecific properties responsible for the observed biological effects. Our analysis led to identification of the most prevalent measurement endpoints relevant for the assessment of the immunotoxic potential of the nanotechnology-based products and will support the smooth and safe translation of the new formulations to clinical applications.